Investigationof the Turkish Cultural Adaptation of International Students Living in Turkey - Khanım Eynullayeva; Murat Gökalp; Bedri Yavuz Hatunoglu (Foxton Books, 2021)
In this study, the cultural adaptations of international students studying in Samsun in acculturation processes were examined. The cultural problems that international students inevitably face affect their adaptation to the countries they host. To investigate the effects of the international students' some variables on the cultural adaptation in the context of Turkey constitutes the main objective of this study. In the study, it was examined whether the cultural adaptation levels of international students vary according to gender, place of residence, academic achievement level, education level, faculty they attend, and their age. Within the scope of the research, 670 foreign students participated in this study. According to the research results, the general adaptation level of the students is medium. While the participants' age is a factor affecting cultural adaptation, the students' cultural adaptation does not change according to their gender, place of residence, level of education, academic performance, and the faculties they attend.